Synergistic Effects of Synthesized Copper Nanoparticles on Escherichia coli and Staphylococcus aureus - A. Leema Rose; F. Janeeta Priya; S. Vidhya (Chemistry and Biochemistry: Research Progress Vol. 3, 2025)
Research in nanomaterials has achieved considerable attention because of their unique properties and numerous applications in different areas. The synthesis of metal nanoparticles has gained significant attention due to their diverse applications. Copper nanoparticles, known for their unique properties, cost-effective production, and wide-ranging uses in catalysis, antimicrobial activity, cooling fluids, and conductive inks, have been a major focus of research. This study compares the stability and antibacterial efficacy of biologically and chemically synthesized copper nanoparticles of two distinct nanometer scales. In chemical synthesis, copper sulfate serves as the precursor, ascorbic acid (vitamin C) as the reducing agent, and polyethylene glycol (PEG) as the capping agent. In biological synthesis, the aqueous root bark extract of Sansevieria trifasciata, valued for its medicinal properties, acts as both the reducing and capping agent. The synthesized Cu-NPs were characterized using UV-Vis spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS) to determine their size, structure, and composition. Their antibacterial activity was assessed by evaluating inhibition zones against different microbial strains. It can be concluded that the copper nanoparticles synthesized by bio-reduction technique are well-dispersed, within the nanometer range and it is of greater stability compared to that of the chemically synthesized copper nanoparticles.